Understanding Occupational Injury and Substance Use Issues among Workers in the Shellfish and Lobster Industries - Johnson, Tora; Darling, Katherine; Kantor, Debra; Spiller, Joseph; Jones, Oliver; Kuntz, Lois-Ann; Casimir, Tara; Dowley, Amy; Kurtz, Greyson; Sachs, Lauren; Silka, Linda; McGreavy, Bridie (Maine Policy Review, 2023)
In 2022, American lobster (Homarus americanus) and softshell clam (Mya arenaria) harvests contributed $283 million to Downeast Maine’s economy, employing thousands of harvesters. Harvesting is grueling work. Pain from work-related injuries precedes most opioid deaths, and workers in fisheries are disproportionately at risk. Harvesters are typically self-employed and often uninsured or underinsured, complicating access to care. Prior studies have focused on injury risk or drug use among harvesters without revealing how injury, pain and substance use intertwine with cultural, social and regulatory factors. This study examined the socio-ecologically embedded injury/ pain/ substance use process with surveys of harvesters (n=106) and healthcare providers and advocates (n=31) followed by interviews of harvesters (n=13) and providers (n=8). We found that harvesters are extremely prone to injury from myriad causes. Shellfish harvesters were more injury-prone and socially vulnerable than lobster harvesters. Deferral of care, problems with healthcare access, age, lack of cultural competency among healthcare providers, and challenges with financial stability were linked to poor outcomes. Interviewees shared many anecdotes of addiction and overdose stemming from injury. Self-medication with substances other than opioids was also prevalent, indicating widespread pain-related challenges. Participants reported family disruption and incarceration related to substance use disorder, and common comorbidities included hepatitis-C, HIV and organ failure. Consultation with community partners yielded recommendations to support health and keep Maine's fisheries afloat, including community-embedded healthcare services, fisheries policy arrangements that reduce injury risk and incentivize health, financial education for managing boom and bust cycles, and expanded insurance programs.
Keywords: fisheries workers; occupational injury; chronic pain; community resilience; marine resources policy; lobster; shellfish